(untitled) (Plant Tissue Culture and Biotechnology, 2009)
A rapid in vitro multiple shoot regeneration protocol has been developed in culture of Boerhaavia diffusa. Shoot tips and nodal segments of field grown plants were used as explants and cultured on MS supplemented with different concentrations and combinations of BAP, Kn and NAA for multiplication of shoots. Maximum multiple shoots were found in MS supplemented with 1.5 mg/l BAP and 0.5 mg/l NAA. After three weeks when they were subcultured in the same medium, the number of shoots per culture increased. Addition of coconut milk in the medium enhanced the number of shoots per culture. For best rooting, well-developed shoots were excised and implanted individually in rooting medium containing half strength of MS fortified with 1.0 mg/l each of IBA and IAA. Ninety per cent of the cultured shoots produced roots within four weeks of culture. Regenerated plantlets were successfully acclimated and established in soil. About 80% plantlets survived under field conditions. Key words: Regeneration, Multiple shoots, Boerhaavia diffusa, Explants D.O.I. 10.3329/ptcb.v18i1.3265 Plant Tissue Cult. & Biotech. 18(1): 49-56, 2008 (June)